PENGEMBANGAN MODUL BERBASIS PROJECT BASED LEARNING PADA MATA PELAJARAN PENATAAN PRODUK KELAS XI DI SMKN 4 SURABAYA - Jannah, Nur Aisyatul; Sudarwanto, Tri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research is development research that collects quantitative and qualitative data through questionnaires, interviews and observations. The instrument used for data collection was a validation sheet in the form of a questionnaire with a 1-5 Likert scale which was used to assess whether the instrument created was valid or not. This validation sheet consists of four types, namely in this approach the researcher distributes questionnaires to media experts, material experts, product management teachers, and class XI students who are also provided with questionnaire answers. This research aims to create a product arrangement module as a form of education. This Product Setup module includes an instructional manual, resources, practice questions, summaries, and self-reflection. This product arrangement module is intended to attract the attention of class XI online business students in understanding content related to creating product display arrangements. Prior to testing, the media was validated by material experts and media experts, with